2004
DOI: 10.1097/00042728-200406000-00029
|View full text |Cite
|
Sign up to set email alerts
|

Telepathology as an Aid in Mohs Micrographic Surgery

Abstract: BACKGROUND. Mohs surgeons are occasionally confronted by challenging pathology ideally requiring the advice of a dermatopathologist. The Internet transmission of digital images of the pathology (telepathology) allows for such opinions to be easily and rapidly obtained. OBJECTIVE. The objective was to obtain images utilizing a digital camera focused directly through one microscope eyepiece with subsequent e-mail to a pathologist for an immediate opinion. METHODS. The particular area of interest on the slide is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…Studies have shown a growing trend and favorable attitudes toward the acceptance of digital pathology by DPs, supporting the likely expansion of this practice in an increasingly digital society . Currently, digital pathology is mostly used for research, medical education, tumor board presentations, archiving and in the healthcare system . The advantages of using digital pathology are apparent.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown a growing trend and favorable attitudes toward the acceptance of digital pathology by DPs, supporting the likely expansion of this practice in an increasingly digital society . Currently, digital pathology is mostly used for research, medical education, tumor board presentations, archiving and in the healthcare system . The advantages of using digital pathology are apparent.…”
Section: Discussionmentioning
confidence: 99%
“…In 2004, Chandra and colleagues described the use of static telepathology for consultation with a remote pathologist during Mohs surgery for evaluation of three cases with challenging pathology and suggested that telepathology provides greater confidence in diagnosis in difficult cases 22 …”
mentioning
confidence: 99%
“…In 2004, Chandra and colleagues described the use of static telepathology for consultation with a remote pathologist during Mohs surgery for evaluation of three cases with challenging pathology and suggested that telepathology provides greater confidence in diagnosis in difficult cases. 22 In this article, we describe our experience with a dynamic telepathology system for intraoperative consultations with a dermatopathologist during Mohs surgery in 61 nonmelanoma skin cancer cases during a 2-year period.…”
mentioning
confidence: 99%